Rancang Bangun Aplikasi Pencatatan Barang Masuk Dan Barang Keluar Pada Gudang PT Telkom Akses Surabaya - Kurniawan, Wahyu Budi Adi; Setyawan, Henry; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: System for recording incoming goods, transfer of goods, and re-filing order goods inventory at the warehouse PT. Telkom Akses Surabaya still using manual systems. The lack of systems that store and archive evidence for a history of the demand for goods. Re-filing goods orders due to inaccurate calculations done using estimates warehouse clerk, inventory resulting void because the goods ordered are yet to come.Need a system that can be used to manage incoming goods, goods out, and re-filing order goods, so inventories of goods in warehouse PT. Telkom Surabaya access can run optimally and not experience emptiness inventory. The system can also print the form of demand for goods that can be used as archival storage.With this system implemented, no longer experienced warehouse inventory vacancy. Reports generated to cleanly and accurately.